Communication and Bible translation - Larsen, Iver (HIPHIL Novum, 2023)
The paper describes the fundamental difference between two types of translations: Literal and meaning-based. It gives an overview of Relevance Theory as a theory of communication that is crucial for a theory of translation. It also discusses 5 criteria used when producing a meaning-based translation. The criteria are illustrated by several examples form English and Danish translations.